Perancangan Sistem Informasi Persediaan Barang Berbasis Web Pada PD.Kopi Ayam Ras - Dilla Dwi Rahmatin Rusfa; Leni Leni (LPPM Politeknik Jambi, 2021)
Kopi Ayam Ras is a company engaged in the storage and sale of goods (distributor). The process of data collection of incoming and outgoing goods, inventory stock, and reporting of goods is not optimal when searching for data due to the large number of data items and data reservoirs still using a manual system. The purpose of this inventory information system is to solve problems that arise in the system that is currently running at PD. Kopi Ayam Ras is also a good solution for companies to create a faster and more accurate inventory management system. Methods of data collection is done by means of interviews, observation, documentation and analysis of the system used by the company. The result of this research is to produce a web-based inventory information system with the FIFO method that provides convenience in providing information on inventory data through incoming and outgoing goods using data flow diagrams, DFD, ERD and MySQL for data processing.